(الشيخ محمد التركي وجهوده الإصلاحية والتربوية في وادي سوف ( بلدة الخبنة بالرقيبة أنموذجا - صالحي، وداد (My University, 2022)
تهدف هذه الدراسة إلى تسليط الضوء على رائد من رواد الإصلاح في الجنوب الشرقي الجزائري، وهو الشيخ محمد التركي، وإبراز جهوده في ترسيخ مقومات الشخصية الجزائرية المتمثلة في الإسلام واللغة العربية والوطنية لدى سكان وادي سوف، في زمن حاول فيه الاستعمار الفرنسي طمسها. وخلصت الدراسة إلى أن رواد الإصلاح المتمثلة في شخص الشيخ محمد التركي، نجحوا في ترسيخ مقومات الشخصية الجزائرية عن طريق الدعوة والتعليم، لدى سكان المناطق الجنوبية الجزائرية، وتكللت بإنشاء مراكز تعليمية تدرس شتى العلوم، لتكون منطلقا في نشر الوعي الديني والوطني تحت ظل جمعية العلماء المسلمين الجزائريين، وأنشئوا جيلا مكافحا للاستعمار الفرنسي، مدافعا عن مقوماته، حاملا راية النهضة الدينية والثقافية في المنطقة. Abstract This study aims to shed light on one of the pioneers of the reform in the southeast area of Algeria, Sheikh Muhammad al-Turki. It also seeks to highlight his efforts in consolidating the components of the Algerian personality represented in Islam, the Arabic language, and patriotism among the residents of Wadi Souf, at a time when French colonialism tried to obliterate them. The study concluded that the pioneers of reform, represented by the personality of Sheikh Muhammad al-Turki, succeeded in consolidating the components of the Algerian personality through advocacy and education, among the inhabitants of the southern Algerian regions. Moreover, this Algerian personality was enthroned by the establishment of educational centers that teach various sciences, as a starting point for spreading the religion and national awareness under the umbrella of the Association of Muslim Algerian Scholars and to create an anti-colonial generation that defends its components, carrying the banner of religious and cultural renaissance in the region
Sheikh Muhammad Al-Turki and his educational reform efforts in Oued Souf (the town of Al-Khbna in Al-Raqeeba as a model
مداخلة
Keywords: محمد التركي؛ الإصلاح؛ وادي سوف؛ المقوماتالشخصية؛ الوطنية; Muhammad Al-Turki; reforma; Wadi Souf; ingredientes; patriotismo.